2006
DOI: 10.1126/science.1118439
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oxygen on Biochemical Networks and the Evolution of Complex Life

Abstract: The evolution of oxygenic photosynthesis and ensuing oxygenation of Earth's atmosphere represent a major transition in the history of life. Although many organisms retreated to anoxic environments, others evolved to use oxygen as a high-potential redox couple while concomitantly mitigating its toxicity. To understand the changes in biochemistry and enzymology that accompanied adaptation to O2, we integrated network analysis with information on enzyme evolution to infer how oxygen availability changed the archi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
356
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 440 publications
(371 citation statements)
references
References 16 publications
10
356
0
5
Order By: Relevance
“…Two derived energy-linked subnetworks stand out in the list, oxygenic mitochondrial ATP synthesis (NRG 00193) and oxygenic photosynthesis (NRG 00195), suggesting these important functions appeared late in evolution, well after discovery of most enzymatic activities. This is consistent with molecular and geological records that suggest life achieved considerable complexity before the appearance of oxygen in the atmosphere, and with enzyme distribution in aerobic pathways that suggests adaptation to oxygen occurred after major prokaryotic divergences in the tree of life (21). Subnetworks with many ancient folds belonging to the remaining mesonetworks, amino acid metabolism (AAC), carbohydrate metabolism (CAR), lipid metabolism (LIP) and nucleotide metabolism (NUC), were clearly ancestral and part of the early enzymatic burst.…”
Section: Most Enzymatic Functions Were Discovered At the Start Of Thesupporting
confidence: 71%
“…Two derived energy-linked subnetworks stand out in the list, oxygenic mitochondrial ATP synthesis (NRG 00193) and oxygenic photosynthesis (NRG 00195), suggesting these important functions appeared late in evolution, well after discovery of most enzymatic activities. This is consistent with molecular and geological records that suggest life achieved considerable complexity before the appearance of oxygen in the atmosphere, and with enzyme distribution in aerobic pathways that suggests adaptation to oxygen occurred after major prokaryotic divergences in the tree of life (21). Subnetworks with many ancient folds belonging to the remaining mesonetworks, amino acid metabolism (AAC), carbohydrate metabolism (CAR), lipid metabolism (LIP) and nucleotide metabolism (NUC), were clearly ancestral and part of the early enzymatic burst.…”
Section: Most Enzymatic Functions Were Discovered At the Start Of Thesupporting
confidence: 71%
“…Many of the microbes have experienced high levels of oxygen relative to their ancestors for several million years, such that the differences we report are a conservative estimate of the extent to which oxygen may have historically limited proteome composition. This work adds to a growing body of literature connecting atmospheric oxygen levels with macroevolutionary changes, most recently with complexity in metabolic networks 28 and cell types 29 . In order to understand the broad role of oxygen levels in major transitions, further investigation and cooperation between the fields of palaeoclimatology, evolutionary biology and bioinformatics are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the study by Raymond and Segrè 38 found that aerobic bacteria have approximately a 1.5 fold increase in the number of reactions and metabolites relative to anaerobic bacteria, resulting in the expansion of metabolic networks evolving in the presence of oxygen, and thus supporting the view of oxygen induced network complexity.…”
Section: Aerobicmentioning
confidence: 82%